Effects of the Informal Cross Border Trade in Western Africa: A Study of Nigeria and Niger - Ahmodu Tijani Ismail Shola; Dosunmu Kazeem Olanrewaju (STIM LASHARAN JAYA MAKASSAR, 2020)
Informal Cross Border Trade (ICBT) plays an important role in developing countries and act as accelerator of economic development, regional development of the borderland areas. It is a crucial coping measure for poor households; especially when unemployment is high and it also address mass poverty if the rules governing it take into consideration the interests of the poor and vulnerable groups in society. This paper is aimed at examining the effects of informal cross border trade in western Africa: a study of Nigeria and Niger, its strength and weakness on National and Regional development which is western Africa. This is a literature and library based paper which reviews related literatures from journal articles, texts, seminar papers, online search engines for assessment of the concepts. This paper perceive the following issues in Informal Cross Border Trade, its problem and approaches, reasons for ICBT in Nigeria and Niger, critical analysis of determinants in Nigeria and Niger, the positive and negative effects on the two selected countries in western African and recommend on way forward. It finds out that ICBT enables small‐scale entrepreneurs to escape poverty and to meet the education, housing and other basic needs. It’s also source of family income to the unemployed and a source of employment to our second citizen as a result of early retirement. It recommends that there should be bilateral agreement between Nigeria and Niger on creating an enabling, gender-sensitive environment for informal cross border traders so that they can easily engage in economic activity in order to protect their livelihoods. There is need to design appropriate policy incentives by the duo country governance in order to gradually incorporate a thriving ICBT sector into the formal economy.